ANALYSIS OF THE INFLUENCE OF GROSS DOMESTIC PRODUCT (GDP), EXCHANGE AND OIL PRICESTHE WORLD ON THE STATE BUDGET DEFICIT IN INDONESIA - Waqqosh, Abi; Hasibuan, Heny Liya; Muda, Iskandar; Soemitra, Andri; Sugianto, (The journal of contemporary issues in business and government, 2021)
This research is a quantitative type of research that aims to determine the relationship between GDP, Exchange Rate and Oil Prices on the State Budget Deficit. The variables used in this study consisted of 3 independent variables and 1 dependent variable. The sample in this study is Indonesia from 1988 to 2018. The analysis model uses Partial Least Square with the help of the WarpPls 7.0 application. Partial Least Square is a statistical data analysis methodology that is at the intersection between regression models, structural equation models, and multiple table analysis methods. The results show that gross domestic product has a significant negative effect on the APBN deficit, the exchange rate has an insignificant negative effect on the APBN deficit, and oil prices the world has an insignificant positive effect on the state budget deficit.